KINERJA GURU PENDIDIKAN AGAMA ISLAM BERSERTIFIKASI DI SMK NEGERI 1 BATANG ANGKOLA TAHUN AJARAN 2017/2018 - Gulo, Nur’ainun (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
Efforts to improve teacher performance are through teacher certification programs. Teacher certification is a process of competency testing for candidates or teachers who want to gain recognition and improve competence according to their chosen profession. This certification is a proof of recognition of the competence of teachers or prospective teachers who meet the standards for doing professional teaching work at certain types and levels of education. In other words teacher certification is fulfilling the need to improve professional competence. The problem to be examined in this study is how is the performance of certified Islamic education teachers in SMK Angkut 1 Batang Angkola academic year 2017/2018. This study aims to determine the performance of certified Islamic education teachers. This research was conducted on Islamic religion teachers in SMK Angkola State, located on Jl. Lintas Sumatra, Batang Angkola District, South Tapanuli. Where all respondents in this study were Islamic religious education teachers who had passed the certification. Through the certification that has been obtained, it is expected to be able to influence the performance of respondents who are getting better so as to produce professional educators. The method in this research is a type of field research with a qualitative approach. The subjects in this study were school principals and certified Islamic education teachers. In this study, the data collection methods used were documentation, observation and interviews to obtain data on the Performance of Certified Islamic Education Teachers in State Vocational High School I Batang Angkola Academic Year 2017/2018. From the results of this study, it was concluded that the Performance of Certified Islamic Religious Teachers in State Vocational School 1 Batang Angkola Academic Year 2017/2018. An increase in the performance of certified Islamic religious education teachers in the aspects of learning plans and implementation.